2019
DOI: 10.1038/s41598-019-54595-z
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neurodynamics changes mediate the efficacy of a personalized neuromodulation against multiple sclerosis fatigue

Abstract: The people with multiple sclerosis (MS) often report that fatigue restricts their life. Nowadays, pharmacological treatments are poorly effective accompanied by relevant side effects. A 5-day transcranial direct current stimulation (tDCS) targeting the somatosensory representation of the whole body (S1) delivered through an electrode personalized based on the brain MRI was efficacious against MS fatigue (FaReMuS treatment). This proof of principle study tested whether possible changes of the functional organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 47 publications
(44 reference statements)
0
85
0
Order By: Relevance
“…They used a tailored procedure with personalized electrodes based on the patients' brain MRI located in place through an MRI-guided neuronavigation system. In a more recent study of this group, the importance of the individual baseline neural networks activity has been outlined as a further parameter for individualized treatment (110). The results of their studies support the efficacy of personalized tDCS approaches.…”
Section: Neurophysiology As Innovative Treatment For Fatigue In Ms Pamentioning
confidence: 96%
See 1 more Smart Citation
“…They used a tailored procedure with personalized electrodes based on the patients' brain MRI located in place through an MRI-guided neuronavigation system. In a more recent study of this group, the importance of the individual baseline neural networks activity has been outlined as a further parameter for individualized treatment (110). The results of their studies support the efficacy of personalized tDCS approaches.…”
Section: Neurophysiology As Innovative Treatment For Fatigue In Ms Pamentioning
confidence: 96%
“…The group of Tecchio et al focused on a personalized anodal tDCS approach targeting the whole-body primary somatosensory areas (S1) bilaterally, following the evidence of S1 reduced excitability and M1 hyperexcitability in PwMS with fatigue (109)(110)(111)(112). They used a tailored procedure with personalized electrodes based on the patients' brain MRI located in place through an MRI-guided neuronavigation system.…”
Section: Neurophysiology As Innovative Treatment For Fatigue In Ms Pamentioning
confidence: 99%
“…In addition, recent evidence has demonstrated that in many cases brain signals considered as belonging to a frequency-defined class of brain rhythms do not represent sustained oscillations, but rather brief bouts of activity that are repeated intermittently (i.e., non-rhythmic) [15,16]. Recognition that physiological time series contain "hidden information" that might be captured by non-linear methods such as fractal analysis, may provide crucial and so far overlooked physiological information in healthy and pathological conditions [17][18][19][20]. However, while this type of nonlinear approaches is no longer an issue in the domain of EEG, there are just few applications on the analysis of micro [21] and macro [22,23] structural neuroimaging data.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Recognition that physiological time series contain "hidden information" that might be captured by nonlinear methods such as fractal analysis (FA), may provide crucial and so far overlooked physiological information in healthy and pathological conditions. [32][33][34][35][36][37][38][39] We have shown that FD can be used to dissociate RSNs from EEG data 9 but, to our knowledge, no study has used FD in functional magnetic resonance imaging (fMRI)-derived RSNs. To fill this gap, we used a data-driven approach based on hierarchical clustering to differentiate RSNs based on their functional roles.…”
Section: Introductionmentioning
confidence: 99%